Fatores de risco para Diabetes Mellitus entre pessoas vivendo com HIV/aids em terapia antirretroviral - Franco, Kátia Barbosa (2017)
The objective of the study was to estimate the prevalence of diabetes mellitus (DM) among people living with HIV/aids (PLWHA) using antiretroviral therapy (ART), to identify risk factors for MD in this population and to investigate the association between the sociodemographic and clinical characteristics of the PLHA and the RF associated with DM. This is a cross-sectional study, developed at the Infectology Clinic of the Walter Cantídio University Hospital (HUWC). The sample consisted of 168 patients, selected by non - probabilistic sampling for convenience. People of both sexes, over the age of 18 years, diagnosed for HIV infection, using ART for at least three months and who were followed at the HUWC outpatient clinic participated in the study. Data collection took place from May 2016 to May 2017, through an interview, using a sociodemographic, clinical and epidemiological form. Capillary glycemia, blood pressure, weight, height, body mass index and waist circumference (AC) were checked. The data was organized and tabulated in Microsoft Excel 2017®. The descriptive statistics of the continuous variables involved the calculation of the mean and standard deviation. Comparisons between two different strata relative to the continuous outcome variables were made using the t test for unpaired variables. Associations between sociodemographic and clinical characteristics (independent or explanatory variables), RD related to DM (outcomes) and the occurrence of DM were assessed by the chi-square test. The strength of such association was also evaluated by the determination of the gross odds ratio and its respective 95% confidence interval. In addition, the explanatory variables associated with DM at a significance level of 20% (P <0.20) were selected to integrate the logistic regression model to identify those that constituted RF for DM. For that, the stepwise method was used backward, being the criterion for the removal of the variables of the model defined by the Wald test. The Statistical Package for Social Sciences (SPSS) software version 20.0 was used for statistical procedures. In the results, the majority of the patients were male, single, with ages ranging from 18 to 39 years old, self-reported brown skin color, with 9 to 12 years of schooling, without children, catholic and employed. The sexual exposure category prevailed, most PLWH were heterosexual, did not live with partner and had a serodiscordant partner. The most commonly used antiretroviral drug was lamivudine, followed by tenofovir and efavirenz. The prevalence of DM in the sample was 7.14%, with a total of 12 people diagnosed. Regarding RF for the development of DM in PLHA, smoking, alcoholism, inadequate feeding, increased CA, overweight, age greater than 45 years, family history of DM, and personal history of hypertension were identified. Women were 5.29 times more likely than men to have increased CA (P <0.001). Men (P = .003), married patients (P = .035) with monthly income greater than two minimum wages (P = .035) were more likely to be hypertensive. DM was more present in older PLHA (P = 0.008). The variables and RF that integrated the logistic regression model (P <0.20) were: age, alcohol consumption and time of antiretroviral therapy. It was concluded that PLWHA in use of HAART, due to exposure to the virus, adverse effects of therapy and / or environmental and behavioral RF for DM development, were more likely to develop DM.